Dynamics of Herding Behavior in Cryptocurrency Markets Amid Market Crashes - Muhammed Aslam Chelery Komath; Ozlem Sayılır; Bakhtiyar Garayev; Patrice Racine Dıallo (Journal of Economy Culture and Society)
Herding behavior is expected to intensify with increasing uncertainty in financial markets, especially after jarring structural changes such as thepandemic. For this reason, in this study we examined herding behavior in the cryptocurrency market amid market crashes. Using daily cryptocurrency price data in 02.01.2018 - 22.03.2023 of the 9 most traded cryptocurrencies, the presence of herding behavior was investigated using the cross-sectional absolute deviation (CSAD) method. The dynamics of herding behavior was explored in 3 sub-periods: the Pre-Covid Period, the Covid-19 Period and the Post Market Crash Period after Tesla’s Announcement. We also tested if the largest cryptocurrencies were driving small cryptocurrencies in the 3 sub-periods as well as the whole period. The findings of the study reveal that there is no herding in the market in significant market fluctuations. Moreover, there seems to be no asymmetric herding behavior as we distinguish between up and down markets. Hence, our findings imply rational investment decision-making. Yet, the results indicate that the largest cryptocurrencies are wielding a substantial influence over the rest of the market across the overall period and in the Post Covid Period (Period 2) in both up and down markets. However, in Period 1 and Period 3, the herding of small cryptocurrencies varies depending on whether the market returns are positive or negative. Our findings imply that the dynamics of the herding behavior between large and small cryptocurrencies has shifted with significant market crashes (outbreak of Covid-19, Tesla’s announcement).